2008
DOI: 10.1017/s174217050700213x
|View full text |Cite
|
Sign up to set email alerts
|

Technology, complexity and change in agricultural production systems

Abstract: Technological advances have contributed to impressive yield gains and have greatly altered US agriculture. Selective breeding and directed molecular techniques address biological shortcomings of plants and animals and overcome environmental limitations. Improvements in mechanization, particularly of power sources and harvest equipment, reduce labor requirements and increase productivity and worker safety. Conservation systems, often designed to overcome problems introduced from other technologies, reduce negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 36 publications
2
60
0
Order By: Relevance
“…Trialability relates to whether the innovation can be experimented with on a limited basis, whilst observability is the degree to which the results of the innovation are visible to others. Sassenrath et al (2008) noted that some innovations are driven by a desire to improve yields, whilst others are concerned for the environment. Environmental innovations are those which focus on improvements to land management; the cost associated with the adoption of these innovations is often borne by the individual farmer while society benefits.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Trialability relates to whether the innovation can be experimented with on a limited basis, whilst observability is the degree to which the results of the innovation are visible to others. Sassenrath et al (2008) noted that some innovations are driven by a desire to improve yields, whilst others are concerned for the environment. Environmental innovations are those which focus on improvements to land management; the cost associated with the adoption of these innovations is often borne by the individual farmer while society benefits.…”
Section: Introductionmentioning
confidence: 99%
“…This argument would appear to hold true, as Buttel et al (1990) reported that the environmental innovations in agriculture that have been most widely adopted are those that are commercially oriented, such as minimum tillage. Sassenrath et al (2008) noted that the adoption of innovations by agriculturists is an interaction between a range of external and internal factors, such as political and social pressures and monetary constraints. Whilst there is little doubt that agriculturists seek increased profitability through innovations, they also tend to be quite risk-averse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PA became an attractive idea for most farmers and agriculture experts in developed countries as a method for optimizing agricultural production (Roberts et al 2004;Sassenrath et al 2008;Cook et al 2003). For instance, site-specific agriculture became attractive for delineating productive zones based on soil quality and production (Mann et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Precision and site-specific farming became an attractive idea for most farmers and agriculture experts in developed countries as a method for optimizing agricultural production (Roberts et al, 2004;Sassenrath et al, 2008;Cook et al, 2003) (Mann et al, 2011). Precision agriculture has been based mostly on information technology, high levels of machinery and computation knowledge.…”
Section: Chaptermentioning
confidence: 99%